Personal factors of the driving style - Astreyko, Natalia S. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article is devoted to the theoretical and empirical analysis of relationship between personal factors and driving style. The main part of the theoretical analysis of the concept of «driving style of the car», personal factors of the driving style (psychotism, neuroticism, anxiety, etc.). The obtained results of the empirical investigation are described: the strength and nature of the correlation relationship, regardless of gender, between driving styles (dissociative, risky, angry, high-velocity, distress-redaction, patient, anxious, careful) and personal characteristics, forms of aggression; differences in driving styles, depending on the level of driver’s aggression. The received results allow to study dangerous and aggressive actions of drivers on the road, and so, to increase traffic safety for all road users.
Keywords: driving style; personal factors; aggression; level of aggression